Improving Medical Students’ Safety Injection Behavior In Panembahan Senopati Hospital by Leaflet, Movie, and Intensification - I Nyoman Roslesmana; Kusbaryanto Kusbaryanto; Merita Arini (Berita Kedokteran Masyarakat (BKM), 2018)
Background: In 2006, Yogyakarta contributes 0.8% Hospital Acquired Infection (HAI's) of total HAI's in Indonesia. In 2010 6-16% HAI's occurred in the Teaching Hospital. Sharps injury is one of the causes of HAI's. Center for Disease Control and Prevention (CDC) stated that there was 385,000 sharps injury/year. Sharps injury can cause a pathogen transmission, such as Hepatitis B Virus, Hepatitis C Virus and Human Immunodeficiency Virus and inflict a financial loss up to $71 to $5,000. Data from Colombo, 2012 stated that 95% of 168 medical students experienced sharp injury. In Indonesia from August-October 2008 at Sardjito Hospital  occurred 43.3% sharp injury and some of them was medical students. Panembahan Senopati Bantul Hospital accepts 40 medical students every year. The Revised Injection Safety Assessment Tool (Tool C – Revised) was used to assess how well-behaved the health worker provided injections to enhance sharp safety. Objective : To improve medical student’s safety injection behavior in Panembahan Senopati Hospital. Method: This research is an action research (AR) type. The research is done in two cycles, first, the acting component was leaflets and movie; second was intensification. Students’ safety injection behavior was evaluated by using Revised Injection Safety Assessment Tool (Tool C – Revised), before and after the action.  Results: Before the research, the medical students’ knowledge on sharp safety was 30% until 80% and the action on safety injection was 33,3% until 70%. After the research the knowledge increased is 80% until 100% and the action is 88,9% until 100%. Conclusion: The improvement of sharp safety knowledge in medical students is 10% until 60% and the action of safety injection in medical students is 30% until 66,7%. The result of this study was reported to The Education and Training Committee of Panembahan Senopati Hospital